Risk factors associated with surgical site infection in patients with musculoskeletal cancer - Bezerra da Silva , Gerlany Gisely (2023)
Background and objectives: surgical site infections (SSI) continue to be a major concern in orthopedic oncology and pose as great a challenge as cancer recurrence, despite the preventive potential of surgery. SSI can be avoided if evidence-based measures are taken. The objective was to assess the frequency of infections in oncological orthopedic surgeries and associated risk factors and inflammatory markers in a reference hospital in the state of Pernambuco. Methods: the frequency of SSI, the identification of isolated microorganisms, the risk factors and the profile of Th1 and Th2 inflammatory markers (IL-2, IL-4, IL-6, IL-10, TNF and IFN-Ƴ) in patients with musculoskeletal cancer were analyzed. Results: SSI were found in 9.1% of patients undergoing orthopedic surgery. Bivariate analysis revealed that a surgical team comprising more than five members (p=0.041) and the need for intraoperative transfusion (p=0.012) were correlated with a higher risk of SSI. The measurement of ultrasensitive C-reactive protein levels to assess the inflammatory response after SSI showed results that were superior to the reference values for each sample, ranging from >5 to >200mg/dl by the immunoturbidimetric method. Of the IL-2, INFγ and TNF (Th1) and IL-4, IL-6, IL-10 (Th2) levels, only interleukin 6 showed high levels, between 6.68 and 58.76 pg/mL. Conclusion: the study found that surgical team with five or more members and blood transfusion were factors associated with the development of SSI in orthopedic surgery in patients with musculoskeletal cancer. Among the inflammatory markers, interleukin 6 (IL-6) showed the highest correlation with the outcome.